Penguatan Pendidikan Karakter Melalui Video-Assisted Learning: Studi pada Program Kampus Mengajar di Sekolah Dasar: Strengthening Character Education Through Video-Assisted Learning: A Study on the Campus-Teaching Program in Elementary Schools - Wa Ode Ningsari; Badruddin Badruddin; Ira Irviana (Al-Musannif, 2024)
Technology-based learning media have been proven to increase students' interest and motivation to learn. However, the creation of the media only targets the cognitive domain without considering the character of the students. This study aims to determine the implementation of strengthening character education through video-assisted learning in elementary school students during the Campus-Teaching program. This type of research is qualitative with a case study approach. The object of this research is grade V students of SD Inpres Pabaeng-baeng, Makassar City. Informants consist of principals, teachers, and students. Data collection uses interviews, observation, and documentation techniques. Data analysis uses descriptive qualitative analysis techniques. Data validity testing uses triangulation techniques. The results of the study found that the implementation of strengthening student character education through video-assisted learning with indicators of religious, discipline, and responsibility is not optimal. This study has implications for knowledge of the material not being directly proportional to the improvement of student character. Therefore, the role of teachers as good role models, advisors, and counselors for students is very important.